Homogeneous multigrid for embedded discontinuous Galerkin methods - Lu, Peipei; Rupp, Andreas; Kanschat, Guido (BIT, 2022)
We formulate a multigrid method for an embedded discontinuous Galerkin (EDG) discretization scheme for Poisson’s equation. This multigrid method is homogeneous in the sense that it uses the same discretization scheme on all levels. In particular, we use the injection operator developed in Lu et al. (IMA J Numer Anal, 2021) for HDG and show optimal convergence rates under the assumption of elliptic regularity. Our analytical findings are underlined by numerical experiments.